Growth of scale for juvenile chinook salmon in the Bolshaya River (West Kamchatka) - Victor F. Bugaev; Nadezhda V. Yarosh (Известия ТИНРО, 2014)
Scale structure is investigated for juvenile chinook salmon caught in the lower part of the Bolshaya River (West Kamchatka) in 2007-2013. Sclerites are formed in late May - late September for underyearlings (on average 9.34 days for a scleritis) and in late May - middle July for the fish of age 1+ (on average 12.76 days for a scleritis). After wintering, the scale seasonal growth resumes and an annual ring is formed usually on May 15-20.